ANALISIS PENERAPAN MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN PADA KPP PRATAMA MUARA TEWEH - Irfan Vemirozan; Vivi Adeyani Tandean (Mount Hope Management International Journal, 2024)
Modernization of the tax administration system is a strategic step in increasing the efficiency and effectiveness of tax services. This research aims to analyze the implementation of modernization of the tax administration system at the Muara Teweh Tax Office, as well as its impact on service quality and taxpayer compliance. The research method used is a qualitative approach with data collection techniques in the form of in-depth interviews, observation and document analysis. The research results show that the implementation of the e-filing, e-billing and e-registration systems has had a positive impact on the tax administration process at Muara Teweh Tax Office. However, there are still several challenges faced, such as resistance to change from some employees and taxpayers, limited technological infrastructure, and lack of socialization regarding the use of modern systems. Therefore, the recommendations put forward include improving technological infrastructure, intensive training for employees, wider outreach to taxpayers, as well as regular monitoring and evaluation to assess the effectiveness of implementing this modern system. This research concludes that the modernization of the tax administration system at Muara Teweh Tax Offiice has succeeded in improving service quality and taxpayer compliance, although improvements are still needed in several aspects to optimize the results